ANALYSIS OF CUSTOMER SATISFACTION OF ORNAMENTAL PLANTS RENTAL IN CV PUTRA TANI - Putrie Nurdiantiwi; Retno Lantarsih; Sulistiya MP (Fakultas Pertanian, Universitas Janabadra, 2018)
The research aims are to: (1) find out the rental property attributes of CV Putra Tani plants that need to be improved in order to increase customer satisfaction of CV Putra Tani; (2) analyze the level of customer satisfaction. Research location determined by purposive sampling in CV Putra Tani. Sampling was done by probability sample method by taking 100 rental consumers of ornamental plants as respondent. Data collected in form of primary and secondary data. To achieve the purpose of the first research using Likert scale scaling with Method of Importance Performance Analysis (IPA). To achieve the purpose of research goals used Method Customer Satisfaction Index (CSI). Based on the research results, the attributes included in the main priority are varieties of plants, the uniqueness of plants, the affordable price, and the suitability of the price with the quality of service and product quality. The result of the analysis of consumer satisfaction index by 0,74762, which mean that consumer including on satisfied criterion.